Age-specific reference values for normal urethral length derived from cross-sectional analysis and implications in hypospadias management - Yan Li; Junfeng Zhao; Jing Zhang; Hehe Chen (Scientific Reports)
Abstract To define age-related ranges for normal urethral length in different pediatric age groups and to demonstrate the clinical impact of using these reference ranges during hypospadias repair. cohort of 501 male children and adolescents (aged 0–18 years) requiring indwelling catheters during hospitalization was enrolled. Urethral and penile lengths were measured, and participants were stratified into eight age groups. Additionally, 47 hypospadias patients undergoing urethroplasty were randomly divided into two groups: Group A (empirical catheter depth: 13–15 cm) and Group B (the 95th percentile of measurement-based catheterization depth). Postoperative symptoms were compared between groups. Mean urethral length was 12.8 cm (SD = 3.3), showing strong positive correlations with age, height, weight, and BMI (Spearman’s ρ = 0.66–0.88, p < 0.001). Group B exhibited fewer postoperative symptoms (hematuria, pain, urinary overflow) than Group A (χ2 = 23.44, p < 0.05 and χ²=23.17, p < 0.0001). Our center cross-sectional study systematically established, for the first time, age-related reference ranges for normal urethral length in pediatric populations, filling a gap in the standardization of developmental anatomy. The application of these reference values in hypospadias repair surgery demonstrated that individualized urethral reconstruction catheterization based on age groups partly reduced postoperative complication rates.